Allium hoshabicum a new species of A. sect. Codonoprasum (Amaryllidaceae) from Van (Turkey) - Firat, Mehmet (Phytotaxa, 2017)
A new species, Allium hoshabicum (A. sect. Codonoprasum), is described from Hoşab/Van province, Turkey. From the morphological point of view, it appears to be similar to Allium huber-morathii, but it differs in several morphological features including scape height, outer tunics shape of bulb, inner tunics colour of bulb, leaf width, umbels size or number, and gynoecium features. A comprehensive description of this species is provided, including detailed illustrations and photographs, geographical distribution, habitat and ecology, vernacular names, and IUCN conservation status.